The Effect of Job Satisfaction And English Teacher's Job Stress on Student's Learning Achievement at Junior High School In Lubuklinggau - astri Riance; Herlina Herlina; Sinta Sinta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT This study aims to determine the effect of job satisfaction and job stress honorary English teachers on English learning achievement of students at Junior High School in Lubuklinggau.The sample used in this study was 30 honorary teachers of English subject at Junior High School. Based on the research results, it is known that a = 11.785, b1 = 0.165, b2 = 0.231. Based on the equation Y=a+b1X1+b2X2, it can be seen that = 11.785 + 0.165X1 + 0.231X2. With the analysis that a was 11.785, it mean that if the Honorary English Teacher did not take Job Satisfaction and Job Stress, the Student's English Learning Achievement will be 11.785, it means that if the teacher make an increase of 1 unit of Job Satisfaction, there will be an increase in the Student's English Learning Achievement by b1 = 0.165, b2 of 0.231 it mean that if the agency make an increase of 1 unit on Work Stress, it will reduce Student Learning Achievement by 0.243, it can be said that the variables of Job Satisfaction and Job Stress on Students' English Learning Achievement have a simultaneous influence. Key Word : Job Satisfaction, English Teachers, Job Stress, Students achievement